IMPROVING CHILDREN'S RECEPTIVE LANGUAGE THROUGH FAIRY TALE VIDEO TUTORIAL LEARNING MEDIA IMPLEMENTATION - Mulyani, Nelly; Noor, Agus Hasbi; Nurhayati, Sri (IKIP Siliwangi Bandung, 2025)
AbstractThe background of this study was that PAUD SPS Anggrek 21 students have mainly not shown receptive language skills which important to improve the language skills of PAUD students. Learning media requires innovation. Theories used in this research are learning media or teaching media and language proficiency theory. The method used in this study was qualitative descriptive method. Data collection techniques include observations, interviews, and documentation studies. The informants in this study were: one principal, one teacher, and 15 students aged 4-5 years who were randomly selected. The location of the study at SPS Anggrek 21 Tanimulya.The results of research on the implementation of teaching media with fairy tale video tutorials to improve receptive language skills in children show that the implementation of teaching media with fairy tale videos can improve children's receptive language skills. This can be seen based on the results of observations that have been made where students have been able to show an increase in receptive language skills. One of the implementation's accomplishments is the learning media employed. Keywords: Receptive Language, Learning Media, Fairy Tale Video Tutorial, Early Childhood .